Development, characterization, and optimization of Losartan-Hydrochorothiazide loaded poly (D,L-Lactide-co-glycolide) (PLGA) nano particles. - Bacud, Karen Joy B.; Bacud, Karen Joy B. Geron; Elyza Marie Santos, Maraiah Shannen T.; Casauay, Jean Flor C.
Hypertension is a prevalent chronic discase that requires patient compliance for successful therapy. However, patients become non-adherent and discontinue medication due to complexity of medication, required dosing frequency, and undesirable drug reactions. Losartan- hydrochlorothiazide (HCTZ), a widely used combination antihypertensive therapy, requires once to twice daily doses. However, conventional preparations of losartan and hydrochlorothiazide have few disadvantages due to low bioavailability of losartan and poor solubility and side effects of HCTZ. Different drug delivery systems are used to address these problems, with nanotechnology incorporated to enhance drug delivery systems. Poly(D,L-lactide-co-glycolide) (PLGA) - a synthetic biodegradable polymer for nanoparticle (NP) drug delivery system - is most commonly used for its biocompatibility, biodegradability and drug loading versatility. Polyvinyl alcohol (PVA), a surfactant in PLGA formulations, decreases interfacial tension and prevents nanoparticle coalescence. Different formulations of losartan-HCTZ loaded PLGA nanoparticles were prepared using modified double-emulsion solvent evaporation from Verma et al. (2013) and tested for surface morphology, particle size, particle size distribution, zeta potential, percent encapsulation efficiency (%EE), and in vitro drug dissolution. All formulations had spherical nanoparticles, smooth surfaces, and mean particle sizes 617 nm - 1022 nm. All formulations were polydispersed and had low zeta potential. Entrapment efficiencies were 31.90% - 37.66% for losartan and 27.60% - 54.80% for HCTZ. PLGA and PVA concentrations had mainly affected the physicochemical characteristics of nanoparticles and the %EE of losartan and HCT. In vitro drug release profiles of all formulations were longer than conventional drug release profiles. Optimized formulation was not achieved since all formulations were not able to meet some of the criteria set.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, May 2019
Keywords: Losartan -- Nanoparticles -- Drug delivery systems -- Optimization; Hydrochlorothiazide -- PLGA nanoparticles -- Characterization; Losartan-HCTZ.; PLGA; PVA; nanoparticles; double emulsion solvent evaporation